PERSONEL OPERATOR AVIOBRIDGE PERFORMANCE ANALYSIS ON ON-TIME PERFORMANCE AT I GUSTI NGURAH RAI BALI INTERNATIONAL AIRPORT - Rafii Rabbani, Muhammad; Syahrul Munir, Muhammad; Idyaningsih, Nining; Komalasari, Yeti (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
This research was conducted to determine the performance of personnel operating aviobridges concerning on-time performance at I Gusti Ngurah Rai Bali International Airport. I Gusti Ngurah Rai Bali International Airport is one of the airports in Indonesia with a considerable number of flights, especially international ones, making it a significant reflection of aviation in the country. This study employed a quantitative descriptive method with a hypothesis testing approach and determination test, using data collection techniques such as observation and questionnaires. The results of this study revealed a positive influence of personnel operator aviobridge performance on on-time performance, with a significance value of the relationship between personnel performance and on-time performance being 0.000 < 0.05. The strong impact of personnel operator aviobridge performance on on-time performance was measured at 60.8%, as obtained from the R-square value in the determination test, while 39.2% was influenced by other aspects not examined in this research